2016
DOI: 10.1002/jcla.21996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the Vicinity of LGALS‐3 Gene and LGALS‐3 mRNA Expression in Advanced Carotid Atherosclerosis: An Exploratory Study

Abstract: Our exploratory results suggest that while rs2274273 and rs17128183 bear no association with the risk of advanced CA or CA-related complications, these genetic variants are likely to affect LGALS-3 expression levels. In order to reach a definitive conclusion on the role played by rs2274273 and rs17128183 in advanced CA, our results should be further validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
7
0
4
Order By: Relevance
“…Based on these data, the authors proposed a molecular mechanism by which Gal-3 modulates not only inflammation, but also vascular osteogenesis, with its expression necessary to acquire a complete osteoblast-like phenotype by VSMCs. Another study highlighted that Gal-3 over-expression in VSMCs induced collagen type I increased synthesis [50], supporting its role as a remodelling factor of the vascular wall [51].…”
Section: Gal-3 In Inflammation and Atherosclerosismentioning
confidence: 92%
“…Based on these data, the authors proposed a molecular mechanism by which Gal-3 modulates not only inflammation, but also vascular osteogenesis, with its expression necessary to acquire a complete osteoblast-like phenotype by VSMCs. Another study highlighted that Gal-3 over-expression in VSMCs induced collagen type I increased synthesis [50], supporting its role as a remodelling factor of the vascular wall [51].…”
Section: Gal-3 In Inflammation and Atherosclerosismentioning
confidence: 92%
“…Unlike our observations, a report by Zhang et al (41) showed that both SNPs rs2274273 and rs4644 gene variants of LGALS-3 were associated with cardiovascular diseases in the Chinese population. Djordjevic et al (42) found that SNP rs2274273 gene variant was associated with LGALS-3 mRNA levels of expression in atherosclerosis tissue of human carotid plaque. Also, Djordjevic et al (13) found that rs2274273 SNP was significantly associated with relative expression levels of LGALS-3 with left-ventricular maladaptive remodelling and HF occurring six months after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Djordjevic et al [42] found that SNP rs2274273 gene variant was associated with LGALS-3 mRNA levels of expression in atherosclerosis tissue of human carotid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-3 is involved in all processes active in atherosclerosis: cell adhesion, cell activation and chemoattraction, cell growth and differentiation [84]. An increase expression of Gal-3 mRNA in human carotid atherosclerotic plaque tissue may be affected by rare genetic variants of the haplotype block, previously associated with Gal-3 circulating levels [85,86]. Diverse cellular processes in atherosclerosis are affected by microRNAs (miRs) and their expression are often tissue and disease-specific [87,88].…”
Section: Role Of Ras In Atherosclerosis Progression and Acute Complicmentioning
confidence: 99%